Bacterial sensitivity assessment of multifunctional polymeric coatings for airway stents. Issue 7 (18th July 2016) - Goodfriend, Amy C.; Welch, Tré R.; Thomas, Collin E.; Nguyen, Kytai T.; Johnson, Romaine F.; Forbess, Joseph M.
Abstract: Current interventional technology for pediatric airway obstruction consists of cardiovascular stents and silicon tubes. These devices are composed of permanent materials that have limitations in biocompatibility and mechanical properties that make them controversial for used in pediatrics. Bioresorbable stents offer a temporary intervention that dissolves in the body over time and can serve as a platform for local drug delivery. Here we investigate a novel approach to use an antibiotic, ciprofloxacin, as a polymerization initiator to synthesize poly(ciprofloxacin fumaric acid) (PCFA) and then a second polymer using gadodiamide as an initiator to synthesize poly(gadodiamide ciprofloxacin fumaric acid) (PGCFA). Polymer structure, degradation, thermal properties, and rheological behavior were analyzed. Ciprofloxacin released was determined and polymer degradation extracts were used in bacterial sensitivity assessments with four common airway pathogens. PCFA and PGCFA polymers and drug release properties were compared to our previously published polymer poly(fumaric acid) (PFA). These novel polymers enable new possibilities as coatings for bioresorbable biomedical applications that require antibiotic resistance and imaging capabilities. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 105B: 2153–2161, 2017.